The science curriculum based on STEM approach with Islamic perspective and its effect on Improving love of learning among 9thstudents in Gaza - Al-Hidabi, Dawood Abdulmalek Yahya; Abu Owda, Mohammed F. (International Organization of Scientific Research (IOSR), 2019)
The current study aimed at revealing the effect of integrative STEM approach from an Islamic perspective in improving love of learning among talented students of 9th grade at science course, and the study followed the Quasi-experimental approach according to pre-post design for one case, as the study sample was (20) talented students of 9th at Mustafa Hafez School. To answer the study main question, love of learning scale was used. The results showed that there are statistically significant differences in the result of love of learning scale between the pre and post application, also it showed that there is an effect to use science course that based on integrative STEM approach from an Islamic perspective in teaching science, this is as a result to overcome the problems that face teachers during presenting the scientific knowledge.